Acute ataxia in paediatric emergency departments: a multicentre Italian study. Issue 8 (4th August 2019) - Garone, Giacomo; Reale, Antonino; Vanacore, Nicola; Parisi, Pasquale; Bondone, Claudia; Suppiej, Agnese; Brisca, Giacomo; Calistri, Lucia; Cordelli, Duccio Maria; Savasta, Salvatore; Grosso, Salvatore; Midulla, Fabio; et al.
Abstract : Objectives: To evaluate the causes and management of acute ataxia (AA) in the paediatric emergency setting and to identify clinical features predictive of an underlying clinically urgent neurological pathology (CUNP). Study design: This is a retrospective medical chart analysis of children (1–18 years) attending to 11 paediatric emergency departments (EDs) for AA in an 8-year period. A logistic regression model was applied to identify clinical risk factors for CUNP. Results: 509 patients (mean age 5.8 years) were included (0.021% of all ED attendances). The most common cause of AA was acute postinfectious cerebellar ataxia (APCA, 33.6%). Brain tumours were the second most common cause (11.2%), followed by migraine-related disorders (9%). Nine out of the 14 variables tested showed an OR >1. Among them, meningeal and focal neurological signs, hyporeflexia and ophthalmoplegia were significantly associated with a higher risk of CUNP (OR=3–7.7, p<0.05). Similarly, the odds of an underlying CUNP were increased by 51% by each day from onset of ataxia (OR=1.5, CI 1.1 to 1.2). Conversely, a history of varicella-zoster virus infection and vertigo resulted in a significantly lower risk of CUNP (OR=0.1 and OR=0.5, respectively; p<0.05). Conclusions: The most frequent cause of AA is APCA, but CUNPs account for over a third of cases. Focal and meningeal signs, hyporeflexia and ophthalmoplegia, as well as longer duration of symptoms, are the most consistent 'red flags' of a severe underlying pathology. Other features with less robust association with CUNP, such as seizures or consciousness impairment, should be seriously taken into account during AA evaluation.